Солдатами не рождаются - Симонов Константин Михайлович (1985)
Экземпляры: Селтинская районная библиотека (аб) (20191106) / Инвентарный номер: 99884 / Авт.знак: С37 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6